Whole-local mechanical analysis and application of long-distance oil and gas pipelines considering dents caused by loading - Yanke Shi; Xinyang Zhang; Leige Xu; Yanjun Chang (Scientific Reports)
Abstract Dental defects are relatively common in long-distance pipeline engineering and can lead to permanent plastic deformation of the pipeline, compromising its structural integrity. To clarify the evolution process of the dented pipelines in engineering practice, this paper puts forward the method of combining the whole and local calculation to analyze the mechanical behavior of pipeline indentations. Based on the combination of whole and local method, the influence of concentration, bending and internal pressure load on the indentation deformation of long-distance oil and gas pipelines under typical scenarios is explored. The research found that the simulated values of indentation depth largely coincided with the measured values. The Mises stress, equivalent plastic strain, and indentation depth reached their maximum values at the contact edges between the pipeline and the supports, making the contact edge between the pipeline and the support the most unfavorable position. In the significance analysis of loads, it is found that the stress change of the pipeline was significant under concentrated loads. As the internal pressure gradually increased, the pipeline stress exhibited a trend of first decreasing and then increasing. When the internal pressure load is 4 MPa, the Mises stress reached its minimum value. During the service stage of the pipeline, low-load conditions can lead to the elastic recovery of indentation deformation in the pipeline, but high-load conditions will exacerbate the indentation deformation, which is detrimental to the continued service of the pipeline. In this study, the mechanical analysis of long-distance oil and gas pipeline is carried out by combining the whole and local, which provides a new technical idea and guarantee for the development of long-distance oil and gas pipeline mechanical analysis industry.